The Relationships Between Need-Supportive Interactions With Peers and Teachers, Perceived Academic Control, and Academic Success - Mohamedhoesein, Nasser (Advances in Social Sciences Research Journal, 2020)
This study discusses the relationships between students' need-supportive interactions, perceived academic control, and academic success. The survey involved 192 undergraduate students from different applied sciences universities in The Netherlands. The study examined if students' interactions with peers and teachers, in support of their needs (relatedness, autonomy, and competence), would improve perceptions of academic control and academic success. The constructs of perceived academic control, basic psychological needs, and students’ formal and informal interaction with peers and teachers were linked to each other in a path model. The findings of path analysis showed that need-supportive interactions predicted positive perceptions of academic control and academic success. Most relevant to positive perceptions of academic control were students' formal interactions with peers and teachers supporting their autonomy and competence. Positive perceptions of academic control subsequently supported academic success.